2014
DOI: 10.1021/tx400434b
|View full text |Cite
|
Sign up to set email alerts
|

Epimers of Azaspiracids: Isolation, Structural Elucidation, Relative LC-MS Response, and in Vitro Toxicity of 37-epi-Azaspiracid-1

Abstract: Since azaspiracid-1 (AZA1) was identified in 1998, the number of AZA analogues has increased to over 30. The development of an LC-MS method using a neutral mobile phase led to the discovery of isomers of AZA1, AZA2, and AZA3, present at ~2-16% of the parent analogues in phytoplankton and shellfish samples. Under acidic mobile phase conditions, isomers and their parents are not separated. Stability studies showed that these isomers were spontaneous epimerization products whose formation is accelerated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…Recent studies on the toxicity of some purified AZA analogues relative to AZA-1 showed that all analyzed AZAs were toxic and that AZA-2, AZA-3, and AZA-6 were more toxic than AZA-1 by 8.3, 4.5, and 7 times, respectively [10], 37-epi-AZA-1 was 5 times more toxic [11], AZA-33 and AZA-34 were 5 times less toxic and 5 times more toxic, respectively [17], and AZA-36 and AZA-37 were 6 and 3 times less toxic, respectively [15]. As major differences in toxicity can be related to slightly different structures of AZAs, the actual toxicity of the different compounds produced by the Mediterranean A. dexteroporum is worthy of consideration in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the toxicity of some purified AZA analogues relative to AZA-1 showed that all analyzed AZAs were toxic and that AZA-2, AZA-3, and AZA-6 were more toxic than AZA-1 by 8.3, 4.5, and 7 times, respectively [10], 37-epi-AZA-1 was 5 times more toxic [11], AZA-33 and AZA-34 were 5 times less toxic and 5 times more toxic, respectively [17], and AZA-36 and AZA-37 were 6 and 3 times less toxic, respectively [15]. As major differences in toxicity can be related to slightly different structures of AZAs, the actual toxicity of the different compounds produced by the Mediterranean A. dexteroporum is worthy of consideration in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, several analogues of AZA-1 have been discovered either in shellfish [7][8][9][10][11] or in dinoflagellates [6,[12][13][14][15][16][17] and structurally characterized by tandem mass spectrometry (MS/MS) and partly also by nuclear magnetic resonance (NMR) spectroscopy. Some AZAs (AZA-1 and AZA-2, among others) are actually produced by the dinoflagellates, whereas others (e.g., AZA-3 to AZA-19) seem to derive from biotransformation occurring in shellfish [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments, including LSE with matrix matched calibration, MSPD with standard addition, and both LSE and MSPD with dilution, were conducted to support the values used for certification (ESM). The neutral pH mobile phase provided resolution of AZA epimers [25] from the parent peak as established previously [16] ( F i g .1A). Molar responses of the 37-epi-AZAs [25] are approximately equivalent to the parent toxins under the LC-MS conditions used.…”
Section: Azaspiracidsmentioning
confidence: 93%
“…The neutral pH mobile phase provided resolution of AZA epimers [25] from the parent peak as established previously [16] ( F i g .1A). Molar responses of the 37-epi-AZAs [25] are approximately equivalent to the parent toxins under the LC-MS conditions used. Epimer peak areas corresponded to approximately 6.5-7.5 % of total peak areas for AZA1, -2, and -3.…”
Section: Azaspiracidsmentioning
confidence: 93%
“…The occurrence of isomeric forms of the major AZA analogs was previously reported [35], and these have recently been characterized as C37 epimers [49]. The presence of these epimers in CRM-AZA-Mus is illustrated in Fig.…”
Section: Certification Measurementsmentioning
confidence: 64%